TECHNOLOGY OF CREATING RELIABLE PROGRAMS - Голуб, Сергій; Салапатов, Володимир (SWorldJournal, 2023)
This work deal with the creation of program models with the help of their description by means of temporal logic. As a result, a program model is created in the form of a non-deterministic finite automatons. Using this model, you can create programs in an